EVALUATION OF FIRE HANDLING TRAINING IN IMPROVING TECHNICAL SKILLS AND WORK DISCIPLINE OF SECURITY PERSONNEL AT HOTEL MERCURE AND IBIS SAMARINDA - Sindi Aulia; Ummi Nadroh (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The internal safety training at Hotel Mercure and Ibis Samarinda aims to enhance the technical skills, work discipline, and knowledge of employees particularly the security team in handling fire emergencies. The training employed an evaluative method with a descriptive quantitative approach, consisting of three main stages: situation analysis and program design, training implementation, and result evaluation. The program was conducted through realistic fire simulations using Fire Extinguishers (APAR), hydrants, and fire balls. Participants were trained in several scenarios, including fire extinguishing, victim evacuation, and first aid, emphasizing teamwork and coordination. The evaluation results showed a significant improvement in participants’ technical skills, particularly in mastering firefighting tools and maintaining effective coordination during simulations. Furthermore, work discipline also improved, as reflected in participants’ punctuality, adherence to procedures, and individual responsibility. This training not only strengthened employee preparedness in dealing with fire hazards but also contributed to building a sustainable safety culture within the hotel environment.